Effect of chronic activity-based therapy on bone mineral density and bone turnover in persons with spinal cord injury - Astorino, Todd Anthony (2013)
PURPOSE: Osteoporosis is a severe complication of spinal cord injury (SCI). Many exercise modalities are used to slow bone loss, yet their efficacy is equivocal. This study examined the effect of activity-based therapy (ABT) targeting the lower extremities on bone health in individuals with SCI. METHODS: Thirteen men and women with SCI (age and injury duration = 29.7 ± 7.8 and 1.9 ± 2.7 years) underwent 6 months of ABT. At baseline and after 3 and 6 months of training, blood samples were obtained to assess bone formation (serum procollagen type 1 N propeptide (PINP) and bone resorption (serum C-terminal telopeptide of type I collagen (CTX), and participants underwent dual-energy X-ray absorptiometry scans to obtain total body and regional estimates of bone mineral density (BMD). RESULTS: Results demonstrated significant increases (p < 0.05) in spine BMD (+4.8 %; 1.27 ± 0.22–1.33 ± 0.24 g/cm(2)) and decreases (p < 0.01) in total hip BMD (−6.1 %; 0.98 ± 0.18–0.91 ± 0.16 g/cm(2)) from 0 to 6 months of training. BMD at the bilateral distal femur (−7.5 to −11.0 %) and proximal tibia (− 8.0 to −11.2 %) declined but was not different (p > 0.05) versus baseline. Neither PINP nor CTX was altered (p> 0.05) with training. CONCLUSIONS: Chronic activity-based therapy did not reverse bone loss typically observed soon after injury, yet reductions in BMD were less than the expected magnitude of decline in lower extremity BMD in persons with recent SCI.